Hubungan Kejadian Pandemi Covid 19 Dengan Kecemasan Ibu Hamil Trimester Tiga - Aslinda Hafid; Hasrul Hasrul (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Objective : Pregnancy is one of the crowning moments in the life of women (Yuniastari et al., 2014). according to the Federasi Obstetri Ginekologi Internasional, Pregnancy defined as fertilization or union of spermatozoa and ovum and followed by nidasi or implantation. If counted and fertilization to this baby, normal gestation time would be held for 40 week or 10 month or 9 moon rotate international calendar. at this time corona virus desease The case go global begins with pneumonia or chafe paru-paru mysterious 2019 on december. When that happens the pandemic covid 19 that directly impact to all indonesian people in general. In the world health of pregnant women also did not escape the effects of the pandemic covid 19 this.The number of pregnant women third trimester there dipustu arawa it makes it very anxious in dealing with the delivery processMetodhe : Methods used is Desain Observasional Deskriptif. In this study , researchers will assess the degree or rate of anxiety for pregnant women third trimesterResults: This study has been implemented in march - april 2021 at pustu arawa That is in the work area puskesmas lawawoi kabupaten sidrap with the total sample 48 respondents . The sample technique used is simple random sampling Pregnant women and patients who came third trimester pustu arawa in the work area puskesmas lawawoi kabupaten sidrap Selected at random. Conclusion: The research found that there was a correlation between the pandemic covid 19 with anxiety pregnant women got the third trimester p = 0.002 < 0,05